Risco relacionado ao consumo de drogas de abuso entre trabalhadores da construção civil : avaliação pelo método do rastreamento - Gavioli, Aroldo (2012)
The construction industry is one economic activity of great importance for Brazil, but is considered one of the world's most dangerous and drugs of abuse is associated with the occurrence of accidents in yours workers. Whereas there is a lack of scientific production of knowledge about the risk level associated with drugs of abuse among construction workers, the aim of this study was to perform the screening of drugs of abuse use among these workers. Cross-sectional, descriptive and quantitative, conducted with 446 construction workers in a medium-sized city in the state of Paraná. Were used structured interview screenplay and the Instrument Alcohol, Smoking and Substance Involvement Screening Test for data collection. Data were analyzed using descriptive statistics (relative and absolute frequency) and bivariate analysis, using Chi Square test. With respect to sociodemographic characteristics of workers, the majority were men, mean aged of 41.1 years (± 12.6), married and with children, one to two minimum wages of remuneration, elementary education level, race/ color white and Catholic. There were statistical significant association between moderate and high levels of drug consumption and low pay, lack of religion, unmarried and no kids. The prevalence of lifetime alcohol use was 91%, tobacco 72.4%, 18.2% marijuana and crack/cocaine 6.7%, higher in workers when compared to general population of Brazilian South Region. The prevalence of current tobacco use (34.1%), alcohol (10.5%), marijuana (2.0%) and cocaine (0.4%) are comparable with the general population. The instrument provides the capability of early detection of workers who have not reached advanced stages of disorders related to drug use, but with potentially risk present. Regarding the use of illicit drugs marijuana and cocaine, individuals have a more experimental use, and for alcohol and tobacco use, the workers showed higher lifetime and current use, denoting that important part of these individuals presents moderate/ high risk for developing health disorders and drug addiction.